Genetic identification of Acetes shrimp from estuary Tanjung Dawai, Kedah using Cytochrome oxidase I (COI) sequences - Maktar, Siti Naqibah (2013)
Species identification by using mitochondrial DNA is a convenient method for species identification. In this study, mitochondrial DNA (mtDNA) partial Cytochrome oxidase I (COI) gene was used to identify Acetes shrimps from Tanjung Dawai, Kedah. DNA was extracted by Promega kit protocols. Out of 15 samples from 18 samples show the presence of DNA bands. However, due to some troubleshooting, the PCR optimization of the Acetes samples failed to be obtained from this study. The unsuitable protocol kit use, the condition and ways of preservation samples as well as amount of Proteinase K use are the major causes that lead to poor yield of DNA product during DNA extraction process. Meanwhile in polymerase chain reaction method, the failures in obtaining PCR products are because of the contamination problems in samples itself, the laboratory surfaces and devices and also the reagent and step apply during the processes. Overall, this study did not fulfill its objective in genetically identifying the shrimp of genus Acetes.